Development of black and biodegradable biochar/gutta percha composite films with high stretchability and barrier properties. (3rd May 2019) - She, Diao; Dong, Juane; Zhang, Junhua; Liu, Lili; Sun, Qianqian; Geng, Zengchao; Peng, Pai
Abstract: It is necessary to develop biodegradable composite films for reducing environmental pollution. Black and biodegradable biochar/gutta percha composite films were developed by adding different contents of biochar (0, 2, 4, 6 and 8%, w/w) into the gutta percha matrix. The results showed that the biochar effectively improved the hydrophobicity and mechanical properties compared with the control film. Moreover, the biochar/gutta percha composite films showed high stretchability and barrier properties. In particular, the 2% BC film had the highest tensile strength (18.3 MPa) and elongation at break (280.4%) and the lowest water vapor permeability value (0.09 × 10 −9 g/m/h/Pa) at 34% relative humidity. However, the melting enthalpy ( ΔH m ) and crystallinity decreased. In addition, these composite films exhibited little electromagnetic interference shielding with a reflection loss up to −1.79 dB at 8.2 GHz. Finally, the composite films were more biodegradable than PE film after 60 days in soil.